Studi Kualitatif Dampak Kebijakan Moneter terhadap Perilaku Konsumen di Kota Semarang - Erlitawati Kaharuddin; Muh Fajrul; Alexader Nova Vernando; Herlin Hidayat (Yayasan Literasi Sains Indonesia, 2026)
This study primarily aims to analyze in depth how monetary policy, specifically the increase in Bank Indonesia's benchmark interest rate, affects household consumption behavior and financial adaptation strategies in Semarang City. The research is motivated by the aggressive monetary tightening policy (150 bps interest rate hike during the 2022–2024 period) which impacted purchasing power in a medium-sized city characterized by high household consumption and diverse financial literacy. Employing a qualitative phenomenological design, data were collected through in-depth interviews with 15 informants from various socio-economic backgrounds, complemented by limited observation and secondary documentation. Thematic analysis, assisted by NVivo 12 software, was conducted to identify patterns of perception, consumption adjustment, and financial responses. The main findings identify four themes: (1) low policy understanding and reactive perceptions among low-income individuals, (2) a significant decline in non-essential and credit-financed durable goods consumption, (3) adaptation strategies such as budget tightening, diversification of digital side income, and a shift in preference toward local/discounted products. A crucial finding highlights behavioral asymmetry based on income: high-income groups respond rationally by increasing deposits and adjusting investments, while low-income groups rely on short-term consumer financing like paylater and make essential expenditure trade-offs. Financial literacy is demonstrated to be a moderating factor, serving as a